SISTEM INFORMASI ADMINISTRASI DESA PANGKALAN BATANG DI KECAMATAN BENGKALIS MENGGUNAKAN FRAMEWORK LARAVEL - Marwati, Leha; Wahyuni, Refni; Yulisman; Muhaimin, Abdi (Riau Journal Of Computer Science, 2020)
Services to the public in the village of Pangkalan Batang are in the form of administrative servicesthe public must come to the village office to find out about service procedures, queue up and get services. The public must also go back and forth to the village office if they lack the conditions for administrative administration. As for the delivery of information about activities carried out in the village carried out by sending letters and through person to person. To overcome this problem, it is proposed that the information administration system of the pangkalan Batang village in the kecamatan bengkalis use the laravel framework, the PHP and MySQL programming language as a database using the waterfall method that can be done computerized so that it becomes faster and more accurate. This application has three parts, namely the village admin, the village head (village head) and the public. This application features the printed letter of being unable, birth letter, marriage letter, parental consent, not related to marriage and gender correctness for administrative arrangements implemented in pdf format. In addition, in this application the public can see information about news, agendas and documentation of village activities in the form of an up-to-date gallery of Pangkalan Batang Village.